2019
DOI: 10.3390/md17050259
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transporters in Prorocentrum lima and Their Expression Under Different Environmental Conditions Including Okadaic Acid Production

Abstract: Prorocentrum lima is a typical benthic toxic dinoflagellate, which can produce phycotoxins such as okadaic acid (OA). In this study, we identified three ABC transporter genes (ABCB1, ABCC1 and ABCG2) and characterized their expression patterns, as well as OA production under different environmental conditions in P. lima. We found that the three ABC transporters all showed high identity with related ABC proteins from other species, and contained classical features of ABC transport proteins. Among them, ABCG2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…(Fernández et al, 2003;Hoppenrath et al, 2013;Luo et al, 2017;Pan et al, 2017;Nishimura et al, 2020). For example, all reported Prorocentrum lima strains produce OA and some strains also produce DTX1 as a minor toxin (Jackson et al, 1993;McLachlan et al, 1994;Vanucci et al, 2010;Varkitzi et al, 2010;Hoppenrath et al, 2013;Wang et al, 2015;Hou et al, 2016;Lee et al, 2016;Hoppenrath, 2017;Pan et al, 2017;Aquino-Cruz et al, 2018;Gu et al, 2019). Prorocentrum belizeanum, caipirignum, concavum, maculosum and hoffmannianum are also known producers of DSP toxins (Morton et al, 1994;Zhou and Fritz, 1994;Hoppenrath et al, 2013;López-Rosales et al, 2014;Luo et al, 2017;Accoroni et al, 2018;Rodríguez et al, 2018;Lim et al, 2019;Lee et al, 2020).…”
Section: Toxic Bioactive Metabolites Frommentioning
confidence: 99%
See 3 more Smart Citations
“…(Fernández et al, 2003;Hoppenrath et al, 2013;Luo et al, 2017;Pan et al, 2017;Nishimura et al, 2020). For example, all reported Prorocentrum lima strains produce OA and some strains also produce DTX1 as a minor toxin (Jackson et al, 1993;McLachlan et al, 1994;Vanucci et al, 2010;Varkitzi et al, 2010;Hoppenrath et al, 2013;Wang et al, 2015;Hou et al, 2016;Lee et al, 2016;Hoppenrath, 2017;Pan et al, 2017;Aquino-Cruz et al, 2018;Gu et al, 2019). Prorocentrum belizeanum, caipirignum, concavum, maculosum and hoffmannianum are also known producers of DSP toxins (Morton et al, 1994;Zhou and Fritz, 1994;Hoppenrath et al, 2013;López-Rosales et al, 2014;Luo et al, 2017;Accoroni et al, 2018;Rodríguez et al, 2018;Lim et al, 2019;Lee et al, 2020).…”
Section: Toxic Bioactive Metabolites Frommentioning
confidence: 99%
“…It has been speculated that the low chlorophyll a to carbon ratio is responsible for the slow growth of dinoflagellates (Tang, 1996) but the chlorophyll a content per unit mass of dinoflagellates is similar to diatoms (Gallardo- Rodríguez et al, 2012). Several studies have focused on small-scale cultures of benthic dinoflagellates to optimize growth rates and toxic production (Jackson et al, 1993;McLachlan et al, 1994;Morton et al, 1994;Yang et al, 2008;Zhong et al, 2008;Li et al, 2009;Vanucci et al, 2010;Varkitzi et al, 2010;López-Rosales et al, 2014;Wang et al, 2015;Hou et al, 2016;Accoroni et al, 2018;Aquino-Cruz et al, 2018;Gu et al, 2019;Lee et al, 2020). In a typical photosynthetic culture the maximum biomass concentration reached was well below 1 g/L and regarding phycotoxin production it is of the order of picograms (Gallardo- Rodríguez et al, 2012).…”
Section: Culture Of Dinoflagellatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prorocentrum lima is another toxic dinoflagellate, which can produce phycotoxins such as okadaic acid (OA). Gu and co-workers [ 45 ] here identify three ABC transporter genes (ABCB1, ABCC1 and ABCG2) and characterize their expression patterns as well as OA production under different environmental conditions in P. lima . For example, they observed that Cu 2+ exposure could up-regulate ABCB1, ABCC1 and ABCG2 transcripts, suggesting a defensive role of ABC transporters against metal ions in surrounding waters.…”
Section: Special Issue Findingsmentioning
confidence: 99%